The Role of CD4 T Cell Memory in Generating Protective Immunity to Novel and Potentially Pandemic Strains of Influenza - DiPiazza, Anthony; Richards, Katherine A.; Knowlden, Zackery A. G.; Nayak, Jennifer L.; Sant, Andrea J. (Frontiers in Immunology, 2016)
Recent events have made it clear that potentially pandemic strains of influenza regularly pose a threat to human populations. Therefore, it is essential that we develop better strategies to enhance vaccine design and evaluation, to predict those that will be poor responders to vaccination and to identify those that are at particular risk of disease-associated complications following infection. Simplified animal models have revealed the discrete functions that CD4 T cells play in the developing immune response and to influenza immunity. However, humans have a complex immunological history with influenza through periodic infection and vaccination with seasonal variants, leading to the establishment of heterogeneous memory populations of CD4 T cells that participate in subsequent responses. The continual evolution of the influenza-specific CD4 T cell repertoire involves both specificity and function and overlays other restrictions on CD4 T cell activity derived from viral antigen handling and MHC class II:peptide epitope display. Together, these complexities in the influenza-specific CD4 T cell repertoire constitute a formidable obstacle to predicting protective immune response to potentially pandemic strains of influenza and in devising optimal vaccine strategies to potentiate these responses. We suggest that more precise efforts to identify and enumerate both the positive and negative contributors within the CD4 T cell compartment will aid significantly in achievement of these goals.